2023
DOI: 10.1186/s12941-023-00600-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundant diversity of accessory genetic elements and associated antimicrobial resistance genes in pseudomonas aeruginosa isolates from a single Chinese hospital

Abstract: Objectives Pseudomonas aeruginosa has intrinsic antibiotic resistance and the strong ability to acquire additional resistance genes. However, a limited number of investigations provide detailed modular structure dissection and evolutionary analysis of accessory genetic elements (AGEs) and associated resistance genes (ARGs) in P. aeruginosa isolates. The objective of this study is to reveal the prevalence and transmission characteristics of ARGs by epidemiological investigation and bioinformatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…13 IMEs typically utilize conjugation mechanisms encoded by other MGEs to achieve transfer and integration 14 while ICEs mainly use tyrosine/serine recombinases or DDE transposases for chromosomal integration and excision. 15 In previous study, a number of novel MGEs were identified in P. aeruginosa in China, such as the novel Inc groups: Inc p60512−IMP and Inc pPA7790 ; 16 Tn6852-related IMEs carrying bla PER-1 and bla CARB-2 : Tn6853; 17 Tn6417-related ICEs carrying bla VIM-1 : Tn6953; 18 and Multiple Tn1403-related transposons carrying different class 1 integrons: Tn6847, Tn6849, Tn7454, Tn7484, etc. 16,17,19 Multiple types of novel MGEs are frequently identified in China, which pose unknown challenges to the containment of bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 IMEs typically utilize conjugation mechanisms encoded by other MGEs to achieve transfer and integration 14 while ICEs mainly use tyrosine/serine recombinases or DDE transposases for chromosomal integration and excision. 15 In previous study, a number of novel MGEs were identified in P. aeruginosa in China, such as the novel Inc groups: Inc p60512−IMP and Inc pPA7790 ; 16 Tn6852-related IMEs carrying bla PER-1 and bla CARB-2 : Tn6853; 17 Tn6417-related ICEs carrying bla VIM-1 : Tn6953; 18 and Multiple Tn1403-related transposons carrying different class 1 integrons: Tn6847, Tn6849, Tn7454, Tn7484, etc. 16,17,19 Multiple types of novel MGEs are frequently identified in China, which pose unknown challenges to the containment of bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…15 In previous study, a number of novel MGEs were identified in P. aeruginosa in China, such as the novel Inc groups: Inc p60512−IMP and Inc pPA7790 ; 16 Tn6852-related IMEs carrying bla PER-1 and bla CARB-2 : Tn6853; 17 Tn6417-related ICEs carrying bla VIM-1 : Tn6953; 18 and Multiple Tn1403-related transposons carrying different class 1 integrons: Tn6847, Tn6849, Tn7454, Tn7484, etc. 16,17,19 Multiple types of novel MGEs are frequently identified in China, which pose unknown challenges to the containment of bacterial resistance. It is necessary to pay close attention to the emergence of novel MGEs and their genetic evolution characteristics.…”
Section: Introductionmentioning
confidence: 99%